Technical - Tactical Actions of Young Football Players in Attack Organization (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article describes how important it is for the player to improve the technical and tactical movements, the movement and technical activity of the player, the transition during one-on-one meetings and various initial situations, the high technical qualities developed for the effective performance of the game.